Confronting Professional and Cultural Barriers to Evidence-Based Teaching in University English Departments: An Auto-Ethnographic Study - Md. Saiful Alam; Adelina Asmawi; Mohammad Hamidul Haque (Online Learning In Educational Research (OLER), 2024)
education, yet their integration in higher education remains underexplored, with most studies focusing on schools. This study aims to identify cultural and professional barriers hindering EBTP adoption among university lecturers through an autoethnographic approach. Using Flanagan's Critical Incident Technique (CIT) and personal journaling, longitudinal qualitative data were collected and analyzed within an interpretive framework. The findings reveal that deeply ingrained cultural capital and traditional professional practices significantly obstruct the adoption of EBTP, highlighting resistance to pedagogical innovation, peer learning, and student-centered teaching. These barriers emphasize the need for institutional reforms, professional development initiatives, and a cultural shift to foster evidence-based practices in higher education, contributing to bridging the gap between research and practice in pedagogy.